The contribution of MMT to modern macroeconomics - Martin J. Watts; James Juniper (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
This paper draws on nearly 25 years of modern monetary theory (MMT) scholarship to provide an assessment of the critique of MMT by Drumetz/Pfister in their 2021 working paper. The present paper commences with a review of methodology. It then pursues a thematic approach, initially exploring the issue of currency sovereignty and the nature of modern monetary systems before addressing the specific criticisms that Drumetz/Pfister have raised about MMT's approach to monetary and fiscal policy.
Keywords: B22; E42; E52; E62; 330; institutional practice; fiat currency; monetary policy; fiscal policy